The importance of spirituality dimensions in the development of entrepreneurship - Hani Sirine; Elisabeth Penti Kurniawati (Diponegoro International Journal of Business, 2018)
Human being as spiritual being needs to be nurtured spiritually so that they can be optimal in their work and their calling. Actualization of this calling can be made through entrepreneurship. The purpose of this study is to determine the importance of spiritual dimensions (vision, faith/hope, love altruistic, meaning/calling, membership) in the development of entrepreneurship (entrepreneurship intention, entrepreneurial networking, entrepreneurial capability, and entrepreneurial success). The analysis technique of this study uses multiple linear regressions with a sample of 67 graduates of Universitas Kristen Satya Wacana (UKSW) who have had and run their own business. The results show that the spirituality dimensions (vision, faith/hope, altruistic love, meaning/calling, membership) significantly influence entrepreneurial intention, entrepreneurial networking, entrepreneurial capability, and entrepreneurial success. When it is tested partially, the significant positive effect on entrepreneurial intention is vision and faith/hope. Faith/hope also has significant positive effects on entrepreneurial networking. Vision, faith/hope, and meaning/calling has significant positive effects on entrepreneurial capabilities. Lastly, faith/hope, and meaning/calling has significant positive effects on entrepreneurial success.